PKM Peningkatan Kemandirian Umkm Melalui Penggunaan Aplikasi Penyusunan Laporan Keuangan Pada Usaha Waroeng Cemilan Amimi - Raya Hasibuan; Mardelia Desfrida; Siti Asnida Nofianna; Amrizal Amrizal (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The general purpose of implementing this activity is as a form of higher education tri dharma activities which are carried out every year using DIPA Polmed funds. While the special objective is to improve the ability of MSMEs in the business world and participate in efforts to develop regional economic capacity. PKM activities have been carried out at the Waroeng Cemilan Amimi Business. Community Partnership Service (PkM) activities are carried out with a focus on the development of MSMEs called Waroeng Cemilan Amimi. Through the implementation of PKM, assistance is carried out to increase the understanding of business owners related to making simple financial statements to support their business continuity. In addition, in response to the impact of the COVID-19 pandemic on the business, assistance was provided in the form of chest freezers and electric ovens to increase efficiency and product diversification. The results of this PkM activity show an increase in the understanding of Waroeng Cemilan Amimi owners in preparing financial statements, so that they are able to manage their business better. The provision of additional equipment such as chest freezers and ovens has helped in expanding production as well as increasing product competitiveness. Thus, this PKM activity has succeeded in making a positive contribution to the sustainability and development of local MSMEs, in line with efforts to support microeconomic recovery during the pandemic. Keywords: Waroeng amimi snacks, financial management, MSME production